DENTAL MANAGEMENT NEEDS OF HOSPITALIZED LEUKEMIC PATIENTS (CASE REPORT) - Indriasti Indah Wardhany; Siti Aliyah Pradono (Faculty of Dentistry, Universitas Indonesia, 2015)
Leukemia is myeloproliferative disorders characterized by differentiation and proliferation of malignantly transformed hematopoetic stem cells, leading to suppression of normal cells, causing anemia, thrombocytopenia, and deficiency of normally functioning leukocytes. It has been classified as either acute or chronic and by cell type. The etiology of leukemia, in most cases, is unknown. Dental management of consideration of the leukemic patient should include history, examination, and screening laboratory tests. This case report is about dental management needs on several cases of hospitalized leukemic patients. Most of the patients have had oral hygiene and need an invasive dental treatment. Although, based on laboratory tests and patient overall condition, these patients considered as high-risk patients, the dentists should perform dental to prevent further oral infection severity.